Access to pediatric oncology medicine in Iran: a cross-sectional survey in Urmia - Kiana Baghban; Sadra Nadimi Parashkouhi; Hadi Abbasian; Mehdi Varmaghani; Mehran Noroozi (BMC Pediatrics)
Abstract Background Cancer stands as a significant cause of mortality among children and adolescents, imposing a considerable burden on global healthcare. The World Health Organization (WHO) reports a stark imbalance in the accessibility of cancer medicines between low-income and high-income countries. Due to high prevalence of cancer in Iran and current barriers to access to oncology medicines, this study aims to scrutinize the landscape of pediatric oncology medicine access, considering unique factors such as sanctions and Iran’s economic context. Methods This study was conducted in Urmia (West Azerbaijan, Iran) in 2022. We employed a descriptive cross-sectional design to explore the availability, pricing, and affordability of 21 outpatient medications related to the five most utilized treatment protocols for prevalent pediatric cancers. A systematic survey was carried out using the recognized methodologies of the WHO and Health Action International (HAI). Data extraction was conducted by a trained student using the checklist provided by the WHO. Data analysis was conducted using SPSS software. Results Among the 21 medicines analyzed, 14 had accessibility rates that were below 50%, with one entirely unavailable and 10 exhibiting availability below 25%. Dactinomycin highlighted the highest Median Price Ratio at 4.1, closely followed by Asparaginase at 3.9. Conversely, Cytarabine, Cyclophosphamide, and Filgrastim displayed the lowest Median Price Ratios (MPR) values, each recording an MPR of 0.1. In the assessment of affordability, it is observed that insured patients across all income deciles have the financial means to cover the minimum costs of medicines. Intriguingly, among the various income deciles, only individuals in the 10th decile exhibit the financial capacity to acquire medicines associated with the examined treatment regimens without insurance coverage, with the exception of the ALL (Acute Lymphoblastic Leukemia) regimen. Conclusion This study illuminates the complex challenges surrounding the availability, cost, and affordability of pediatric cancer medications in Urmia, Iran. It is crucial to develop supportive policies that aim to lower medication expenses for patients and improve their access to cancer treatments. Tackling these challenges necessitates a collaborative effort involving stakeholders, policymakers, and healthcare providers.